Comparison of Indian package inserts in public and private sector: an urgent need for self regulation - Mahatme, Mohini S.; Dakhale, Ganesh N.; Hiware, Sachin K.; Wankhede, Sumit S.; Salve, Anoop M.; Mahatme, Sachin R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Package inserts are the authentic source of information for the new molecules in the market. Incomplete and incorrect product information may promote irrational prescribing and may have serious consequences. Hence, our aim was to analyse and compare the information supplied in the package insert according to the section 6.2 and section 6.3 of schedule D of Drugs and Cosmetic Act, 1940 in public (government) and private (non-government) sector. Methods: Package inserts of allopathic drugs which were supplied by government from drug store of tertiary care centre and hospital and from pharmacies on request were collected. A total of 270 package inserts in English were collected that is 38 from government hospital and 232 from the pharmacies nearby the hospital. The package inserts were analysed for the presentation of completeness of the information as per section 6.2 and 6.3. Results: The presentation of information on analysing 233 package inserts (28 government and 205 non government) was not uniform and it was difficult to locate and retrieve information easily due to lack of common layout and heading. Moreover, the package inserts were of variable shape and size with different font size which made it inconvenient for analysing as well as for reference. Posology and method of administration was incomplete in 3% package insert in non- government cases whereas in government supply it was 7%. Use of drug in pregnancy and lactation was deficient in 11% and 14% packages inserts of non-government sources and government sources respectively. Instructions for use were lacking in 25% and 29% package inserts of government and non-government sources respectively. Conclusions: The need of the hour is to further refine contents of the circulated package inserts to make them complete, reliable and up to date. This can be a step forward for ethical and effective dissemination of healthcare services in our growing society.